Antimicrobial Activity of Calcium Silicate-Based Dental Materials: A Literature Review - Ana Cristina Padilha Janini; Gabriela Fernanda Bombarda; Lauter Eston Pelepenko; Marina Angélica Marciano (MDPI AG, 2021)
Endodontic biomaterials have significantly improved dental treatment techniques in several aspects now that they can be used for vital pulp treatments, as temporary intracanal medication, in definitive fillings, in apical surgeries, and for regenerative procedures. Calcium silicate-based cement is a class of dental material that is used in endodontics in direct contact with the dental structures, connective tissue, and bone. Because the material interacts with biological tissues and stimulates biomineralization processes, its properties are of major importance. The main challenge in endodontic treatments is the elimination of biofilms that are present in the root canal system anatomical complexities, as it remains even after chemical-mechanical preparation and disinfection procedures. Thus, an additional challenge for these biomaterials is to exert antimicrobial activity while maintaining their biological properties in parallel. This article reviews the literature for studies considering the antimicrobial properties of calcium silicate-based dental biomaterials used in endodontic practice. Considering the reviewed studies, it can be affirmed that the reduced antimicrobial effect exhibited by calcium silicate-based endodontic materials clearly emphasizes that all clinical procedures prior to their use must be carefully performed. Future studies for the evaluation of these materials, and especially newly proposed materials, under poly-microbial biofilms associated with endodontic diseases will be necessary.